Two-dimensional fullerene covalent network, electrochemical synthesis method and photoelectric detector
Through electrochemical synthesis method, electric-driven quaternary ammonium salt cation intercalation layer containing hydrogen protons and solvated protons are used to in situ reduce the interlayer interaction, and realize efficient stripping of two-dimensional C60 network, solve the problem of insufficient peeling efficiency and quality in the prior art, and have the advantages of efficient large-scale preparation.
Patent Information
- Application Number
- CN202510009844.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-03
- Publication Date
- 2025-04-22
AI Technical Summary
The prior art is difficult to efficiently synthesize a two-dimensional C60 covalent network with a complete structure in large quantities, and the stripping efficiency and quality are insufficient, and it is difficult to expand production.
By electrochemical synthesis method, through the intercalation of the layered fullerene superlattice, an electrically driven quaternary ammonium salt cationic intercalation layer containing hydrogen protons is used, and combined with the solvated proton reduction at the edge of the fullerene superlattice material, the hydrogen bubbles are generated to destroy the interlayer interactions, thereby achieving rapid uniform intercalation and efficient peeling.
The peeling rate of up to 83% is achieved, the reaction time is shortened, the complete crystal structure of the two-dimensional C60 network is retained, the average lateral dimension reaches 52.5μm2, the single layer ratio exceeds 30%, and the average thickness is only 2.1nm, which has the advantages of efficient large-scale preparation.
Smart Images

Figure CN119859809A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of two-dimensional material preparation, and specifically relates to a two-dimensional fullerene covalent network, an electrochemical synthesis method and a photoelectric detector, and particularly relates to Mg4C 60 Crystals and 2D C 60 Efficient bulk synthesis of covalent networks. Background Art
[0002] Superatoms are artificial clusters of the same element or heteroatoms whose charge, size, and composition can be varied to achieve a wide range of functional customization. Since the first discovery of specific superatoms that can mimic the chemical properties of natural atoms, the scientific community has shown great interest in the synthesis of such two-dimensional materials. Further studies have shown that the covalent assembly of superatoms can form two-dimensional materials that are very different in properties from traditional atomic components. Their unique layered electronic structure leads to the overlap of molecular orbitals within and between clusters, which gives the materials completely new physical properties. In addition, because there are almost no restrictions on the customizable structure and chemical properties of superatomic clusters, two-dimensional superatomic materials have the potential to host unknown assembly units.
[0003] Two-dimensional fullerene covalent network (two-dimensional C 60 Network) is a new type of superatomic material composed of pure carbon clusters (C 60 ) are connected to each other by carbon-carbon (CC) covalent bonds to form a hexagonal lattice structure. 60 The molecule is connected to 6 adjacent C 60 Molecular connections, including independent C-C single bonds and [2+2] cycloaddition bonds, form a two-dimensional periodic nanocluster structure. 60 The network is an intrinsically pure carbon semiconductor material with a modest band gap of 1.6 eV, in stark contrast to other carbon materials such as semi-metallic graphene and electrically insulating fullerenes. In addition, theoretical studies have shown that two-dimensional C 60 The networks exhibit excellent strength, (thermo)dynamic stability, low thermal conductivity, high carrier mobility, and outstanding optical / thermoelectric properties. For example, density functional theory (DFT) calculations show that a single-layer 2D C 60 The network has strong covalent bonds and an elastic modulus between 50 GPa and 62 GPa. Molecular dynamics (MD) simulations found that even at temperatures as high as 800 K, the two-dimensional C 60 The network remains stable, and its thermal conductivity is 56.63W / m·K, much higher than C 60 The thermal conductivity of the molecule is 0.3W / m·K to 0.4W / m·K. First-principles calculations reveal that the two-dimensional C 60 The network has an ultra-high hole mobility (1242cm2 ·V -1 ·s -1 ), which is mainly attributed to the large effective mass caused by the flat energy band near the conduction band minimum (CBM). Calculations also show that the two-dimensional C 60 The network has in-plane anisotropy, uniform pore structure and cage-like surface, and is suitable for many fields such as nonlinear optics, solvent separation, energy storage, single-atom catalysis, biomedicine, etc. However, although theoretical predictions show its broad application prospects, due to the lack of two-dimensional C with complete structure and minimum number of layers, it is still difficult to obtain the network. 60 Network, current experimental verification and practical application are still far behind theoretical research.
[0004] Since it is extremely difficult to directly assemble fullerene clusters into a two-dimensional structure, the prior art suggests using fullerene superlattice materials such as Mg4C 60 Crystals as parent materials for indirect synthesis of 2D C 60 Network is a feasible general method. In this method, the two-dimensional C 60 The network is bound by magnesium ions between the layers, forming an ordered superlattice structure along the stacking direction. However, the strength of the C-Mg bond is between covalent bonds and ionic bonds and is significantly stronger than the van der Waals force, which makes it difficult to separate the two-dimensional C using traditional techniques such as mechanical exfoliation. 60 Meirzadeh et al. proposed that Mg 2+ Can be obtained from Mg4C 60 The crystal is partially removed, resulting in a loosely stacked C 60 In this case, mechanical exfoliation can only produce a very small amount of double-layer C 60 In addition, Hou et al. found that spontaneous diffusion of organic cations in solvents could break C-Mg bonds and expand the interlayer distance, thus facilitating the formation of 2D C 60 However, this process requires long reaction times (>168 h), so only milligram quantities of 2D materials can be obtained.
[0005] The main challenge of exfoliation is to overcome the strong interlayer interaction in fullerene superlattice materials while maintaining the fragile 2D C 60 The integrity of the network structure. However, in the prior art including the above-mentioned solution, the two-dimensional C 60 The integrity of the network structure while achieving high efficiency, high quality, high yield and scalable production still needs to be improved. Summary of the invention
[0006] To solve the above problems, the present invention provides a two-dimensional fullerene covalent network and an electrochemical synthesis method and a photodetector. The method is based on the intercalation expansion of layered fullerene superlattice, adopts the strategy of electrically driven insertion of hydrogen-containing proton-containing quaternary ammonium salt cations, and combines the auxiliary effect of in-situ reduction of solvated protons at the edge of the fullerene superlattice material. The generation of hydrogen bubbles destroys the interlayer interaction force, thereby further promoting the rapid and uniform intercalation. The method greatly shortens the reaction time and the stripping rate is as high as 83%. The two-dimensional C after stripping 60 The network maintains a complete crystalline structure with an average lateral size of 52.5 μm. 2 The monolayer ratio is high (>30%), and the average thickness is only 2.1nm. This method has the advantages of short stripping time, high stripping efficiency, and can be used to efficiently prepare two-dimensional C in large quantities. 60 Advantages of the Internet.
[0007] The present invention solves the above technical problems through the following technical solutions.
[0008] One of the purposes of the present invention is to provide an electrochemical synthesis method of a two-dimensional fullerene covalent network, comprising the following steps:
[0009] Using fullerene superlattice material as cathode, inert material as anode, and a mixed solution of quaternary ammonium salt containing hydrogen protons and polar aprotic solvent as electrolyte solution, electrochemical stripping is carried out under constant voltage. Through the in-situ reduction of hydrogen ions driven by the electric field and the rapid and uniform intercalation of quaternary ammonium salt cations, a two-dimensional fullerene covalent network is obtained.
[0010] Furthermore, the concentration of the quaternary ammonium salt containing hydrogen protons in the electrolyte solution is 3 mg / mL to 20 mg / mL.
[0011] Furthermore, the quaternary ammonium salt containing hydrogen protons is at least one of tetra-n-butylammonium hydrogen sulfate, tetra-n-butylammonium hydrogen phosphate, tetra-n-butylammonium hydrogen carbonate, tetra-n-butylammonium hydroxide, and tetra-n-butylammonium hydrofluoride, and the polar aprotic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, propylene carbonate, and acetonitrile.
[0012] Furthermore, the potential of the constant voltage is -4V to -12V, the stripping temperature is -50°C to 200°C, and the stripping time is 2h to 8h.
[0013] Furthermore, the fullerene superlattice material is an alkaline earth metal-doped fullerene covalently assembled superlattice.
[0014] Furthermore, the alkaline earth metal is Mg, Li, Na, K or Rb.
[0015] Furthermore, the fullerene superlattice material is embedded in a porous metal foam support as a cathode.
[0016] Furthermore, after electrochemical stripping, the stripped product is shaken and centrifuged at 800rpm-1200rpm for 3min-15min to obtain an initial product, and then a H2O2 solution with a mass concentration of 2%-5% is added for charge quenching, and centrifuged at 3000rpm-12000rpm for 3min-15min to obtain a two-dimensional fullerene covalent network.
[0017] Furthermore, the electrochemical stripping adopts a two-electrode system or a three-electrode system.
[0018] The second object of the present invention is to provide a two-dimensional fullerene covalent network prepared by the above electrochemical synthesis method, wherein the lateral size of the two-dimensional fullerene covalent network is 0.1 μm to 100 μm and the average thickness is 0.8 nm to 10 nm.
[0019] A third object of the present invention is to provide a photoelectric detector prepared using the above-mentioned two-dimensional fullerene covalent network as a photoelectric response element.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] (1) The present invention provides an electrochemical synthesis method of a two-dimensional fullerene covalent network. Based on the intercalation expansion process of a layered fullerene superlattice, an electrically driven hydrogen-containing proton quaternary ammonium salt cation intercalation strategy is adopted, and the auxiliary effect of in-situ reduction of solvated protons at the edge of the fullerene superlattice material is combined. The generated hydrogen bubbles destroy the interaction force between the layers, thereby effectively promoting the rapid and uniform intercalation. The stripping rate of up to 83% is successfully achieved, which greatly shortens the reaction time, and the fullerene superlattice material is efficiently stripped into gram-level high-quality two-dimensional C that can be processed by solution. 60 This method not only shortens the peeling time and improves the peeling efficiency, but also can efficiently prepare two-dimensional C 60 Online material.
[0022] (2) The electrochemical synthesis method provided by the present invention, the two-dimensional C 60 The network retains a complete crystalline structure with an average lateral size of 52.5 μm 2 , the monolayer ratio exceeds 30%, and the average thickness is only 2.1nm.
[0023] (3) Due to the peeled 2D C 60 The network has a unique hierarchical electronic structure, and C 60 With excellent light-matter interaction, it is possible to 60The thin film photodetector prepared by the network material exhibits a wide spectrum of light response from 405nm to 1200nm, and reaches a peak light response current at 850nm, with a stable and repeatable response time. This efficient top-down synthesis strategy has opened up a new direction for the development of functional two-dimensional super-atomic carbon composite materials and devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 This is a diagram of the electrochemical synthesis process of the two-dimensional fullerene covalent network of the present invention.
[0025] Figure 2 Mg4C 60 Material preparation process diagram.
[0026] Figure 3 Mg4C prepared by the present invention 60 Physical pictures and scanning electron microscope pictures of crystal materials, Figure 3 a in the formula is Mg4C 60 Crystal physical picture, b is Mg4C 60 Scanning electron micrograph of the crystal.
[0027] Figure 4 Mg4C prepared by the present invention 60 Raman spectra and X-ray diffraction patterns of materials, Figure 4 a is the Raman spectrum and b is the X-ray diffraction pattern.
[0028] Figure 5 Mg4C prepared by the present invention 60 Structural changes during electrochemical intercalation of a crystal. Figure 5 a in the figure is Mg4C before electrochemical intercalation on nickel foam 60 crystal, b is Mg4C after electrochemical intercalation on nickel foam 60 Crystal.
[0029] Figure 6 The two-dimensional C prepared by the present invention 60 Network dispersion graph in DMF, Figure 6 a in the figure is the physical dispersion diagram, and b is the optical microscope image.
[0030] Figure 7 The stripping yields of Example 1 of the present invention at different working voltages, electrolyte concentrations and stripping times are shown in FIG. Figure 7 Where a represents different working voltages, b represents different electrolyte concentrations, and c represents different stripping times.
[0031] Figure 8 It is a comparison chart of the stripping methods of Example 1 of the present invention and Comparative Examples 3 to 4.
[0032] Fig. 9The two-dimensional C of the embodiment 1 of the present invention 60 The morphological structure diagram of the network, Fig. 9 a is a SEM image at a scale of 10 μm, b is a SEM image at a scale of 5 μm, c is a TEM image, and d is a high-resolution TEM image and a selected area electron diffraction image.
[0033] Fig.10 The two-dimensional C of the embodiment 1 of the present invention 60 AFM image of the network, Fig.10 a in the equation is a two-dimensional C 60 Large-scale AFM image of the network, b is a single monolayer two-dimensional C 60 Profile of network thickness.
[0034] Fig.11 The two-dimensional C of the embodiment 1 of the present invention 60 Thickness and size distribution plots of the network, Fig.11 a is the thickness distribution diagram, and b is the size distribution diagram.
[0035] Fig.12 Mg4C under different stripping times in Example 1 of the present invention 60 The morphology and structure of the crystal. Fig.12 Here, a is 0 min, b is 5 min, c is 10 min, and d is 15 min.
[0036] Fig.13 This is a morphological diagram of the change in interlayer spacing during the intercalation process of Example 1 of the present invention. Fig.13 a and b in the figure are the morphological changes in the initial stage of intercalation and exfoliation observed at different scales, and c and d are the morphological changes under the assistance of hydrogen ions.
[0037] Fig.14 This is the X-ray diffraction diagram of Example 1 of the present invention at different stripping times.
[0038] Fig.15 This is a graph showing the stripping yield of different cations under the same conditions in the present invention.
[0039] Fig.16 The present invention is different quaternary ammonium salts and single H + Comparison of the monolayer exfoliation rate and nanosheet size after ion intercalation.
[0040] Fig.17 The different intercalation stages of Mg4C 60 EDS energy dispersive spectroscopy elemental analysis diagram of the crystal.
[0041] Fig.18 The present invention shows that Mg4C is intercalated at different reaction times. 60 Line graph of interlayer spacing and atomic proportions of a crystal.
[0042] Fig.19 The two-dimensional C 60 Zeta potential and X-ray photoelectron spectroscopy of the network, Fig.19 a is the Zeta potential diagram, and b is the X-ray photoelectron spectrum diagram.
[0043] Fig. 20 The two-dimensional C 60 Plot of the photocurrent response of the network's photodetectors.
[0044] Fig.21 The two-dimensional C 60 A plot of the photoelectric response of the network's photodetectors at different wavelengths.
[0045] Fig. 22 The two-dimensional C 60 Photocurrent performance diagram of the network's photodetector after varying voltage and light intensity.
[0046] Fig.23 The two-dimensional C 60 Responsivity diagram of the network's photodetector at different bias voltages. DETAILED DESCRIPTION
[0047] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0048] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0049] Two-dimensional fullerene network composed of superatomic C 60 Nanoclusters are composed of covalent bonds and are emerging semiconductor materials with unique layered electronic structures. Fullerene superlattice materials such as Mg4C 60 Crystals as parent materials for the preparation of two-dimensional C 60 The main challenge of exfoliation is to overcome the bulk Mg4C 60 Stronger interlayer interactions in crystals while protecting fragile 2D C 60The existing stripping methods require complex and time-consuming reaction processes, which poses a huge challenge to scalable production and universal application, that is, there is still a lack of a very suitable stripping strategy in terms of high efficiency, high quality and excellent scalability production.
[0050] Based on the above problems, the present invention provides a hydrogen-assisted electrochemical strategy for rapid exfoliation of fullerene superlattice materials into solution-processable, gram-scale, high-quality two-dimensional C 60 Network. Details are as follows:
[0051] A method for electrochemical synthesis of a two-dimensional fullerene covalent network comprises the following steps:
[0052] Using fullerene superlattice material as cathode, inert material as anode, and a mixed solution of quaternary ammonium salt containing hydrogen protons and polar aprotic solvent as electrolyte solution, electrochemical stripping is carried out under constant voltage. Through the auxiliary effect of in-situ reduction of hydrogen ions driven by electric field and the rapid and uniform intercalation of quaternary ammonium salt cations, a two-dimensional fullerene covalent network is obtained.
[0053] The present invention is based on the intercalation expansion process of layered fullerene superlattice, adopts an electrically driven quaternary ammonium salt cation intercalation strategy containing hydrogen protons, and combines the auxiliary effect of in-situ reduction of solvated protons at the edge of the fullerene superlattice material. The generated hydrogen bubbles destroy the interaction force between the layers, thereby effectively promoting the rapid and uniform intercalation. The stripping rate of up to 83% was successfully achieved, greatly shortening the reaction time, and efficiently stripping the fullerene superlattice material into gram-level high-quality two-dimensional C 60 This method not only shortens the peeling time and improves the peeling efficiency, but also can efficiently prepare two-dimensional C 60 Online material.
[0054] In some specific embodiments, the concentration of the quaternary ammonium salt in the hydrogen proton-containing electrolyte solution is 3 mg / mL to 20 mg / mL. Within this concentration range, the optimal auxiliary effect of hydrogen ion in-situ reduction can be achieved, and the excessive generation of bubbles can be avoided to cause the 2D C 60 The fragmentation of the network also avoids the low stripping efficiency caused by insufficient auxiliary effects.
[0055] In some specific embodiments, the quaternary ammonium salt containing hydrogen protons is at least one of tetra-n-butylammonium hydrogen sulfate, tetra-n-butylammonium hydrogen phosphate, tetra-n-butylammonium hydrogen carbonate, tetra-n-butylammonium hydroxide, and tetra-n-butylammonium hydrofluoride, and the polar aprotic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, propylene carbonate, and acetonitrile. In a preferred embodiment, the quaternary ammonium salt containing hydrogen protons is tetra-n-butylammonium hydrogen sulfate, and the polar aprotic solvent is N,N-dimethylformamide. It should be noted that the choice of solvent affects the Mg4C 60 Another key factor in crystal intercalation and stripping is that the present invention uses a polar aprotic solvent, N, N-dimethylformamide (DMF), as a dispersion solvent, which exhibits a strong charge stabilization ability and is conducive to the rapid formation of solvated cations, thereby improving the stripping efficiency. DMF, as a dispersion medium, has the characteristics of a low boiling point (153°C) and a high dielectric constant (36.7). In addition, DMF has a high dielectric constant (36.7) in Mg4C 60 The crystals also exhibit excellent wettability with a contact angle of only 6.3°, which facilitates the efficient intercalation of solvated cations composed of tetra-n-butylammonium hydrogen sulfate (TBA·HSO4).
[0056] In some specific embodiments, the electrochemical stripping process adopts a constant voltage method, the working potential is set between -4V and -12V, the stripping temperature is -50°C to 200°C, and the stripping time is 2h to 8h. This potential range is higher than that of Mg4C 60 The minimum potential window (-3.1V) required for crystal intercalation ensures the smooth progress of the intercalation process. Setting the potential interval at -4V to -12V can achieve the best cation intercalation effect and the best stripping efficiency, while avoiding the possibility of 2D C 60 The phenomenon of network fragmentation, thus maintaining the two-dimensional C 60 Structural integrity of the network and high-quality stripping efficiency.
[0057] In some specific embodiments, the fullerene superlattice material is an alkaline earth metal doped fullerene covalently assembled superlattice. The alkaline earth metal is Mg, Li, Na, K or Rb. More specifically, the alkaline earth metal doped fullerene covalently assembled superlattice includes Mg2C 60 Mg4C 60 ,LiC 60 、Li2C 60 、Li4C 60 、Li6C 60 、Li8C 60 , Li 10 C 60 , Li 12 C 60、NaC 60 、Na2C 60 、Na4C 60 、K3C 60 、K6C 60 or Rb3C 60 .
[0058] In order to break the strong interaction between the layers, the present invention uses Mg4C 60 Take fullerene superlattice materials as an example, the electrochemical synthesis process is as follows Figure 1 As shown, a typical electrochemical intercalation was performed in a two-electrode system using platinum foil as the anode and bulk Mg4C 60 Crystal as cathode, based on layered fullerene superlattice (Mg4C 60 crystals) by electrically driven insertion of hydrogen-containing quaternary ammonium cations and combined with Mg4C 60 The auxiliary effect of in-situ reduction of solvated protons at the edge of the crystal. The generated hydrogen bubbles destroyed the interaction between the layers, thereby effectively promoting the rapid and uniform intercalation, successfully achieving a stripping rate of up to 83%, greatly shortening the reaction time, and converting Mg4C 60 Efficient exfoliation of crystals into gram-scale high-quality solution-processable 2D C 60 This method not only shortens the peeling time and improves the peeling efficiency, but also can efficiently prepare two-dimensional C 60 Network. Stripped 2D C 60 The network retains a complete crystalline structure with an average lateral size of 52.5 μm 2 , the monolayer ratio exceeds 30%, and the average thickness is 2.1 nm.
[0059] In some embodiments, the alkaline earth metal doped fullerene covalently assembled superlattice is Mg4C 60 Crystal, Mg4C 60 Preparation method of crystal material, process diagram as shown Figure 2 As shown, the following steps are included:
[0060] C 60 The magnesium source is placed in the corresponding high and low temperature zones of a dual-temperature zone tube furnace, with the high temperature zone ranging from 550°C to 650°C and the low temperature zone ranging from 450°C to 550°C. Under vacuum conditions, chemical vapor transmission is performed in the transition zone between the high temperature zone and the low temperature zone to obtain large quantities of high-quality Mg4C 60 Crystal.
[0061] It should be noted that the synthesis of large-sized bulk Mg4C 60 Single crystal is the key to realize large-scale two-dimensional C 60The present invention successfully synthesized large-sized, highly crystalline quasi-hexagonal Mg4C in the transition region between two temperature zones of a quartz tube by chemical vapor transport. 60 Single crystal.
[0062] The present invention provides a Mg4C based on dual temperature zone chemical vapor transport (CVT) technology 60 A method for high-quality batch synthesis of crystals. 60 The quartz tube is sealed at both ends by vacuum and placed in a double-zone furnace at 650℃~450℃ for 20h~30h. 60 One end of the magnesium source is placed in the high temperature zone, and one end of the magnesium source is placed in the low temperature zone. 60 The crystals are crystallized and synthesized in the transition zone between the two. A mild nucleation rate and a long reaction time are essential for the growth of large-sized single crystals. By placing a sufficient amount of magnesium source in the low temperature zone, optimal magnesium ion diffusion can be achieved, while also avoiding the reaction of magnesium with the quartz tube at high temperature, thereby effectively preventing the byproduct Mg2C 60 In addition, C 60 Keep it separate from the magnesium source to keep the unreacted C 60 It can be recovered and reused. This method is economical and conducive to large-scale crystal synthesis.
[0063] In some specific embodiments, C 60 The mass ratio of magnesium source is 0.5 to 1.5:1, the temperature range of the high temperature zone is 550°C to 650°C, the temperature range of the low temperature zone is 450°C to 550°C, and the time of chemical vapor transmission is 20h to 30h. A mild nucleation rate and a long reaction time are crucial to the growth of large-sized single crystals. By placing a sufficient amount of magnesium source in the low temperature zone, optimal magnesium ion diffusion can be achieved, avoiding the reaction of magnesium with the quartz tube at high temperature, thereby effectively preventing the byproduct Mg2C 60 The formation of crystals. At the same time, C 60 Keep it separate from the magnesium source to keep the unreacted C 60 It can be recycled and reused. This method is universal and economical, and is conducive to large-scale crystal synthesis.
[0064] In some specific embodiments, the fullerene superlattice material is embedded in porous nickel foam as a cathode. In order to ensure effective contact between the bulk fullerene superlattice material and the electrode, the fullerene superlattice material is wrapped in porous nickel foam.
[0065] In some specific embodiments, after electrochemical stripping, the embedded fullerene superlattice material is transferred from the nickel foam to a DMF solution, and after manual shaking and stripping, the product is centrifuged at 800 rpm to 1200 rpm for 3 min to 15 min to obtain a primary product, and then a H2O2 solution with a mass concentration of 2% to 5% is added for charge quenching, and the product is centrifuged at 3000 rpm to 12000 rpm for 3 min to 15 min to obtain a two-dimensional C 60 network, and the two-dimensional C 60 The network was dispersed in DMF solution and stored for later use.
[0066] In some specific embodiments, the electrochemical stripping adopts a two-electrode or three-electrode system. In a preferred embodiment, the electrochemical stripping adopts a two-electrode system, and the Pt sheet electrode is used as the anode.
[0067] In addition, the present invention provides a two-dimensional C 60 The photodetector of the network film is prepared by the electrochemical stripping method described above. 60 The network was prepared as a photoelectric responsive element.
[0068] Since the two-dimensional C 60 The hierarchical electronic structure of the network, and C 60 With unique light-matter interaction, the thin-film photodetector based on this all-carbon two-dimensional material shows a broad spectrum of light response from 405nm to 1200nm, with a peak photocurrent at 850nm and a stable and repeatable response time. This efficient top-down synthesis strategy paves the way forward for the development of functional two-dimensional superatomic carbon-based composite materials and devices.
[0069] The method for preparing the above-mentioned photoelectric detector comprises the following steps:
[0070] A doped silicon substrate is provided.
[0071] A SiO2 layer is coated on the doped silicon substrate, the thickness of the SiO2 layer is 300 nm, and a patterned drain and source are prepared on the SiO2 layer using photolithography technology.
[0072] A two-dimensional fullerene network film was prepared on a porous polytetrafluoroethylene filter membrane by vacuum filtration. The two-dimensional fullerene network film had a thickness of 200 nm and was then transferred to a SiO2 layer to prepare a photodetector.
[0073] In some specific embodiments, the channel width of the photodetector is 200 μm and the length is 10 μm.
[0074] The invention is further described below through specific examples.
[0075] Example 1
[0076] A two-dimensional C 60 The electrochemical synthesis method of the network comprises the following steps:
[0077] S1、Mg4C 60 Preparation of crystals: 250 mg of magnesium foil and 200 mg of C 60 The powder is vacuum sealed at both ends of the quartz tube, containing C 60 One end of the powder was placed in a high temperature zone with a temperature of 610°C, while the end containing magnesium foil was placed in a low temperature zone with a temperature of 510°C. Under vacuum conditions, the powder was heated in a dual temperature zone furnace at 510°C to 610°C for 24 hours. Chemical vapor transport was performed in the transition zone between the high temperature zone and the low temperature zone to obtain a large amount of high-quality Mg4C 60 Crystalline material.
[0078] S2. Tetra-n-butylammonium hydrogen sulfate and N,N-dimethylformamide (DMF) are mixed to form a tetra-n-butylammonium hydrogen sulfate solution, wherein the concentration of the tetra-n-butylammonium hydrogen sulfate solution is 5 mg / mL, which is used as an electrolyte solution.
[0079] S3, 100 mg of Mg4C wrapped in a porous nickel foam support 60 The crystal was used as the cathode and the Pt sheet was used as the anode, and placed in an electrolyte solution. The electrodes were arranged in parallel at a fixed distance of 2.0 cm. In the absence of inert gas protection, the constant potential was set at -8 V at room temperature for electrochemical stripping. The stripping was stopped after 2 h. After electrochemical stripping, the embedded Mg4C 60 The crystals were transferred from the nickel foam to a DMF solution, and after manual shaking and peeling, they were centrifuged at 1000 rpm for 10 min to obtain the initial product. Then, 3% H2O2 was added for charge quenching, and the product was centrifuged at 8000 rpm for 10 min to obtain the 2D C 60 network, and the two-dimensional C 60 The network was dispersed in DMF solution and stored for later use.
[0080] Example 2
[0081] A two-dimensional C 60 The electrochemical synthesis method of the network comprises the following steps:
[0082] S1、Mg4C 60 Preparation of crystals: 150 mg of magnesium foil and 120 mg of C 60 The powder is vacuum sealed at both ends of the quartz tube, containing C 60One end of the powder was placed in a high temperature zone at 600°C, while the end containing magnesium foil was placed in a low temperature zone at 500°C. Under vacuum conditions, the powder was heated in a dual temperature zone furnace at 500°C to 600°C for 24 hours. Chemical vapor transport was performed in the transition zone between the high temperature zone and the low temperature zone to obtain a large amount of high-quality Mg4C 60 Crystalline material.
[0083] S2. Tetra-n-butylammonium hydrogen sulfate and N,N-dimethylformamide (DMF) are mixed to form a tetra-n-butylammonium hydrogen sulfate solution having a concentration of 15 mg / mL, which is used as an electrolyte solution.
[0084] S3, 100 mg of Mg4C wrapped in a porous nickel foam support 60 The crystal was used as the cathode and the Pt sheet was used as the anode, and placed in an electrolyte solution. The electrodes were arranged in parallel at a fixed distance of 2.0 cm. In the absence of inert gas protection, the constant potential was set at -6 V at room temperature for electrochemical stripping. The stripping was stopped after 4 h. After electrochemical stripping, the embedded Mg4C 60 The crystals were transferred from the nickel foam to a DMF solution, and after manual shaking and peeling, they were centrifuged at 1000 rpm for 10 min to obtain the initial product. Then, 3% H2O2 was added for charge quenching, and the product was centrifuged at 8000 rpm for 10 min to obtain the 2D C 60 network, and the two-dimensional C 60 The network was dispersed in DMF solution and stored for later use.
[0085] Example 3
[0086] A two-dimensional C 60 The electrochemical synthesis method of the network comprises the following steps:
[0087] S1、Mg4C 60 Preparation of crystals: 250 mg of magnesium foil and 300 mg of C 60 The powder is vacuum sealed at both ends of the quartz tube, containing C 60 One end of the powder was placed in a high temperature zone with a temperature of 620°C, while the end containing magnesium foil was placed in a low temperature zone with a temperature of 520°C. Under vacuum conditions, the powder was heated in a dual temperature zone furnace at 520°C to 620°C for 20 hours. Chemical vapor transport was performed in the transition zone between the high temperature zone and the low temperature zone to obtain a large amount of high-quality Mg4C 60 Crystalline material.
[0088] S2. Tetra-n-butylammonium hydrogen sulfate and N,N-dimethylformamide (DMF) are mixed to form a tetra-n-butylammonium hydrogen sulfate solution, wherein the concentration of the tetra-n-butylammonium hydrogen sulfate solution is 10 mg / mL, which is used as an electrolyte solution.
[0089] S3, 100 mg of Mg4C wrapped in a porous nickel foam support 60 The crystal was used as the cathode and the Pt sheet was used as the anode, and placed in an electrolyte solution. The electrodes were arranged in parallel at a fixed distance of 2.0 cm. In the absence of inert gas protection, the constant potential was set at -10 V at room temperature for electrochemical stripping. The stripping was stopped after 2 h. After electrochemical stripping, the embedded Mg4C 60 The crystals were transferred from the nickel foam to a DMF solution, and after manual shaking and peeling, they were centrifuged at 1000 rpm for 10 min to obtain the initial product. Then, 3% H2O2 was added for charge quenching, and the product was centrifuged at 8000 rpm for 10 min to obtain the 2D C 60 network, and the two-dimensional C 60 The network was dispersed in DMF solution and stored for later use.
[0090] Comparative Example 1
[0091] A two-dimensional C 60 The electrochemical synthesis method of the network comprises the following steps:
[0092] S1、Mg4C 60 Preparation of crystals: 250 mg of magnesium foil and 200 mg of C 60 The powder is vacuum sealed at both ends of the quartz tube, containing C 60 One end of the powder was placed in a high temperature zone at 600°C, while the end containing magnesium foil was placed in a low temperature zone at 500°C. Under vacuum conditions, the powder was heated in a dual temperature zone furnace at 500°C to 600°C for 24 hours. Chemical vapor transport was performed in the transition zone between the high temperature zone and the low temperature zone to obtain Mg4C 60 Crystalline material.
[0093] S2. Tetra-n-butylammonium bromide and N,N-dimethylformamide (DMF) are mixed, and the concentration of the tetra-n-butylammonium bromide solution is 5 mg / mL, which is used as an electrolyte solution.
[0094] S3, 100 mg of Mg4C wrapped in a porous nickel foam support 60 The crystal was used as the cathode and the Pt sheet was used as the anode, and placed in an electrolyte solution. The electrodes were arranged in parallel at a fixed distance of 2.0 cm. In the absence of inert gas protection, the constant potential was set at -8 V at room temperature for electrochemical stripping. The stripping was stopped after 2 h. After electrochemical stripping, the embedded Mg4C 60 The crystals were transferred from the nickel foam to a DMF solution, and after manual shaking and peeling, they were centrifuged at 1000 rpm for 10 min to obtain the initial product. Then, 3% H2O2 was added for charge quenching, and the product was centrifuged at 8000 rpm for 10 min to obtain the 2D C 60 network, and the two-dimensional C 60The network was dispersed in DMF solution and stored for later use.
[0095] Comparative Example 2
[0096] A two-dimensional C 60 The electrochemical synthesis method of the network comprises the following steps:
[0097] S1、Mg4C 60 Preparation of crystals: 250 mg of magnesium foil and 200 mg of C 60 The powder is vacuum sealed at both ends of the quartz tube, containing C 60 One end of the powder was placed in a high temperature zone at 600°C, while the end containing magnesium foil was placed in a low temperature zone at 500°C. Under vacuum conditions, the powder was heated in a dual temperature zone furnace at 500°C to 600°C for 24 hours. Chemical vapor transport was performed in the transition zone between the high temperature zone and the low temperature zone to obtain Mg4C 60 Crystalline material.
[0098] S2. Tetra-n-butylammonium hexafluorophosphate and N,N-dimethylformamide (DMF) are mixed to form a tetra-n-butylammonium hexafluorophosphate solution having a concentration of 5 mg / mL, which is used as an electrolyte solution.
[0099] S3, 100 mg of Mg4C wrapped in a porous nickel foam support 60 The crystal was used as the cathode and the Pt sheet was used as the anode, and placed in an electrolyte solution. The electrodes were arranged in parallel at a fixed distance of 2.0 cm. In the absence of inert gas protection, the constant potential was set at -8 V at room temperature for electrochemical stripping. The stripping was stopped after 2 h. After electrochemical stripping, the embedded Mg4C 60 The crystals were transferred from the nickel foam to a DMF solution, and after manual shaking and peeling, they were centrifuged at 1000 rpm for 10 min to obtain the initial product. Then, 3% H2O2 was added for charge quenching, and the product was centrifuged at 8000 rpm for 10 min to obtain the 2D C 60 network, and the two-dimensional C 60 The network was dispersed in DMF solution and stored for later use.
[0100] Comparative Example 3
[0101] A two-dimensional C 60 The liquid phase synthesis method of the network comprises the following steps:
[0102] S1. Purification of C by sublimation 60 Powder, the purified C 60 The powder and Mg powder were mixed and vacuum sealed in a quartz tube, which was then placed in a double-temperature furnace at a temperature of 500°C to 580°C for 20 hours; 60The powder mixture is placed in a high temperature zone with a temperature of 580°C, while the Mg4C 60 The single crystal is grown in the low temperature zone, the temperature of the low temperature zone is 500℃, with a Mg:C ratio of 15:1 60 Molar ratio synthesis of Mg4C 60 Single crystal.
[0103] S2, tetrabutylammonium salicylate was dissolved in N-methylpyrrolidone (NMP) to obtain a saturated solution, and Mg4C 60 The crystals were added to a saturated solution of tetra-n-butylammonium salicylate and soaked for more than 7 days. After manual shaking, a mixture was obtained. The mixture was centrifuged at 1000 rpm for 10 min to remove the precipitate, and then centrifuged at 8000 rpm for 10 min to remove the tetra-n-butylammonium salicylate solution to obtain a two-dimensional C 60 Network, 2D C 60 The network was washed with NMP and finally dispersed in NMP for later use.
[0104] Comparative Example 4
[0105] A two-dimensional C 60 A method for mechanical stripping of a network, comprising the following steps:
[0106] S1. Growth of Mg4C using chemical vapor transport technology 60 Single crystal: C 60 Powder and Mg powder with Mg:C 60 The mixture was mixed in a molar ratio of 6:1, ground into a uniform mixture, pressed into sheets and placed in a quartz tube, and then the tube was sealed under vacuum and placed in a dual-temperature furnace at 500℃~600℃ for 24h and then cooled to room temperature to obtain Mg4C 60 Crystalline, highly air-sensitive Mg4C 60 The crystal grows in the low temperature zone of the quartz tube.
[0107] S2, Mg4C 60 The crystals were immersed in 10% acetic acid or nitric acid aqueous solution for 2 h. The crystals were then immersed in N-methylpyrrolidone (NMP) at 180 °C for 12 h, rinsed thoroughly with tetrahydrofuran, and vacuum dried at 80 °C for 12 h. The treated crystals were peeled off with tape to obtain a double-layer two-dimensional C 60 network.
[0108] The two-dimensional C prepared in Example 1 and Comparative Examples 1 to 4 60 The network was tested for structure and performance, and the results are shown below.
[0109] Figure 3 Mg4C prepared by the present invention 60 Physical pictures and scanning electron microscope pictures of crystal materials, Figure 3 a in the formula is Mg4C 60 Crystal physical picture, b is Mg4C 60 Scanning electron microscope image of the crystal. Figure 3 As shown in the figure, the present invention produces large-sized, highly crystallized quasi-hexagonal Mg4C 60 Single crystal (lateral size is mm). Due to magnesium ion doping, bulk Mg4C 60 The crystals have a metallic luster.
[0110] Figure 4 Mg4C prepared by the present invention 60 Raman spectrum and X-ray diffraction pattern of the crystal, Figure 4 a in the figure is the Raman spectrum, and b is the X-ray diffraction pattern. Figure 4 As shown, the X-ray diffraction (XRD) pattern shows two characteristic peaks at 10.7° and 20.8°, corresponding to (200) and (400) reflections, and the Raman spectrum shows a peak at 1403 cm -1 There is a clear C 60 vibration peak, and at 939cm -1 and 963cm -1 The middle double peaks are attributed to the formation of bridge bonds corresponding to the stretching mode of the four carbon rings. These further confirm that the single-phase Mg4C 60 Successful synthesis of crystals.
[0111] The present invention selects N, N-dimethylformamide (DMF) as the dispersion medium, as shown in Table 1, because it has the characteristics of low boiling point (153°C) and high dielectric constant (36.7). 60 The crystals also exhibited excellent wettability with a contact angle of 6.3°, which facilitated the efficient intercalation of solvated cations composed of tetra-n-butylammonium hydrogen sulfate (TBA·HSO4).
[0112] Table 1 Performance comparison of different dispersion media
[0113]
[0114] In addition to quaternary ammonium cations (TBA + ) intercalation, the reduction of protons (from HSO4 - Ionization of anions) in 2D C 60 Driven by the electric field, these protons move along the Mg4C 60 The edge of the crystal was originally reduced, and hydrogen bubbles were uniformly generated. The dense hydrogen bubbles destroyed the strong interaction between the layers and promoted TBA + The rapid and uniform insertion of cations enables the formation of single-layer or few-layer 2D C60 The hydrogen-assisted effect at the cathode effectively prevents the two-dimensional C 60 The unnecessary oxidation of the network maintains the 2D C 60 The structural integrity of the network.
[0115] Figure 5 Mg4C prepared by the present invention 60 Volume change diagram of the crystal during electrochemical intercalation. Figure 5 a in the figure is Mg4C before electrochemical intercalation on nickel foam 60 crystal, b is Mg4C after electrochemical intercalation on nickel foam 60 Crystal. Figure 5 As shown, Mg4C was monitored by ex situ optical imaging. 60 Volume change during electrochemical intercalation of the crystal. Applying a voltage of -8.0 V results in a rapid and significant volume expansion and the generation of dense hydrogen bubbles.
[0116] Figure 6 The two-dimensional C prepared by the present invention 60 A graph of the network being scattered in DMF, Figure 6 a is the physical dispersion diagram, b is the two-dimensional C 60 Optical microscope image from the Internet. Figure 6 As shown in a, the fully expanded Mg4C 60 It is easy to disperse in DMF and form a uniform high concentration (5 mg / mL) of 2D-C by simple manual shaking. 60 Network dispersion. Figure 6 As shown in b, it shows the closely packed two-dimensional C 60 Optical microscope image of the network.
[0117] The layer yield was calculated gravimetrically by filtration. Figure 7 The stripping yield diagram of Example 1 of the present invention at different working voltages, electrolyte concentrations and stripping times is shown in FIG. Figure 7 a is different working voltage, b is different electrolyte concentration, and c is different stripping time. Figure 7 As shown, the hydrogen-assisted electrochemical stripping strategy achieved a stripping yield as high as 83% within 2 h.
[0118] As shown in Table 2, compared with the prior art such as Comparative Examples 3 and 4, the stripping method of the present invention shows significant advantages in terms of shorter stripping time, higher stripping efficiency, better scalability, etc. The prior art such as the liquid phase stripping method (Comparative Example 3) relies on the spontaneous and uniform diffusion of organic cations into the intercrystalline layers. This process usually takes more than 7 days and is highly sensitive to many factors such as temperature, oxygen and crystal quality.
[0119] Table 2 Comparison of the present invention and the prior art stripping method
[0120]
[0121] Mg4C 60 Cathode expansion of crystals for large-scale production of 2D C in 2 hours 60 The Internet provides a fast and efficient way to Figure 8 1 is a comparison chart of the peeling method of Example 1 of the present invention and Comparative Examples 3 and 4. Figure 8 As shown, the stripping time of this method is at least 84 times faster than that of liquid phase stripping (Comparative Example 3). The effective cation intercalation makes the stripping efficiency of this method as high as 83%, and it is not easily affected by environmental factors, ensuring high repeatability.
[0122] In addition, the present invention is highly scalable by using a large amount of Mg4C 60 crystals and larger electrolytic cells, which can significantly increase the 2D C 60 The output of the network.
[0123] Scanning electron microscopy (SEM), transmission electron microscopy (TEM) and atomic force microscopy (AFM) were used to investigate the 2D C 60 The shape of the network.
[0124] Fig. 9 The two-dimensional C of the embodiment 1 of the present invention 60 The morphological structure diagram of the network, Fig. 9 a is a SEM image at 10 μm scale, b is a SEM image at 5 μm scale, c is a TEM image, and d is a high-resolution TEM image and a selected area electron diffraction image. Fig. 9 As shown, the SEM images show a broad size distribution with lateral dimensions exceeding 10.0 μm. The electric field-driven rapid cation intercalation and the generation of a large number of bubbles did not lead to the formation of 2D C 60 Excessive fragmentation of the network. Through TEM characterization, 2D C 60 The network shows a typical two-dimensional morphology, and its lateral dimensions are consistent with the AFM images. As shown in the high-resolution TEM (HR-TEM) images, the bright spheres arranged in a regular hexagonal lattice correspond to C 60 The selected area electron diffraction (SAED) pattern clearly confirmed the hexagonal lattice structure.
[0125] Fig.10 The two-dimensional C of the embodiment 1 of the present invention 60 AFM image of the network, Fig.10 a in the equation is a two-dimensional C 60 Large-scale AFM image of the network, b is a single monolayer two-dimensional C 60A cross-sectional view of the network thickness. Fig.10 As shown, according to the cross-sectional view in the AFM image, the detached two-dimensional C 60 The thickness of the network is 1.1 nm, corresponding to a monolayer thickness.
[0126] By using optical microscopy and AFM to examine approximately 150 different 2D C 60 Network samples, statistical analysis of the exfoliated 2D C 60 Size (length and width) and thickness distribution of the networks. Fig.11 The two-dimensional C of the embodiment 1 of the present invention 60 Thickness and size distribution plots of the network, Fig.11 a is the thickness distribution diagram, and b is the size distribution diagram. Fig.10 As shown, more than 85% of the exfoliated 2D C 60 The size of the network is larger than 40 μm 2 The average thickness is about 2.1nm, which is equivalent to 2 to 3 layers. It is worth noting that the proportion of exfoliated single layers exceeds 30%, which is caused by hydrogen bubbles. The generation of hydrogen bubbles further expands the interlayer distance and promotes the rapid and uniform insertion of cations.
[0127] The intercalation and exfoliation mechanisms of Mg4C were analyzed in depth. 60 Morphological changes of crystals at different intercalation stages. Fig.12 This is a morphology structure diagram of Example 1 of the present invention at different peeling times. Fig.12 In the equation, a is 0min, b is 5min, c is 10min, and d is 15min. Fig.12 As shown, before intercalation, bulk Mg4C 60 The crystals showed a tightly packed, clear layered structure. After a constant voltage (-8V) was applied to the working electrode for a few minutes, the interlayer spacing of the crystals expanded significantly and the edges became wrinkled.
[0128] Fig.13 This is a morphological diagram of the change in interlayer spacing during the intercalation process of Example 1 of the present invention. Fig.13 a and b in the figure are the morphological changes of different sizes at the initial stage of intercalation, and c and d are the morphological changes caused by the hydrogen ion assistance. Fig.13 As shown, due to Mg4C 60 The interlayer interaction of the crystal is strong. In the initial stage, the intercalation of cations is not uniform. In contrast, hydrogen ions are more likely to enter the interlayer uniformly. The subsequent in-situ reduction helps the precise separation of a few layers or even a single layer. The bubbles destroy the ordered interlayer structure and reduce the interlayer sliding energy barrier, which is TBA. + The rapid intercalation of cations creates space.
[0129] Fig.14 The X-ray diffraction diagram of Example 1 of the present invention at different stripping times. Fig.14 As shown, as the intercalation process proceeds, from the initial Mg4C 60 The interlayer spacing increases significantly from crystals (0.83nm) to intercalation compounds (1.08nm).
[0130] In addition, under the conditions of the synthesis method in Example 1, the present invention uses different cations such as Li + 、Na + 、TMA + 、TEA + , THA + The effect on stripping efficiency, Fig.15 Figure 2 is a graph showing the stripping efficiency of different cations under the same conditions of the present invention. Fig.15 As shown, indicating TBA + is the most suitable intercalation cation, with a diameter of 0.83 nm, similar to Mg4C 60 The interlayer spacing of the crystals (0.84 nm) matches.
[0131] In order to prove that H + and TBA + The interaction between ions was excluded in the system containing tetrabutylammonium bromide (TBA·Br) (Comparative Example 1) or tetrabutylammonium hexafluorophosphate (TBA·PF6) (Comparative Example 2). + . Fig.16 The present invention is different quaternary ammonium salts and single H + Comparison of the single-layer exfoliation rate and nanosheet size after ion intercalation. Fig.16 As shown, separate TBA + It is difficult for cation intercalation to overcome the interlayer interaction, resulting in extremely low exfoliation efficiency and thicker layers. + The ion-driven interlayer expansion is also limited and insufficient to achieve exfoliation.
[0132] From the above, we can see that TBA + Uniform intercalation of cations for 2D C 60 The effective exfoliation of the network is crucial, especially for achieving large lateral dimensions and atomic thickness. The auxiliary effect of hydrogen ions plays an important role in the present strategy, which utilizes the in-situ reduction of hydrogen ions to destroy the Mg 2+ The stronger interlayer interaction established by ions provides TBA + The uniform and rapid insertion of cations creates a more optimal interlayer distance. + and TBA + The synergistic effect between ions is a continuous process, which gradually advances from the edge of the crystal to the middle.
[0133] During the intercalation process, Mg 2+ Effect of ion changes on fullerene superlattice (Mg4C 60 Complete exfoliation of the crystals is also crucial. Fig.17 The different intercalation stages of Mg4C 60 EDS energy dispersion spectrum element analysis diagram of the crystal. Fig.17 As shown, it can be seen that as the reaction proceeds, Mg 2+ We speculate that the hydrogen bubbles destroyed the charge balance at the crystal interface, thereby increasing the disorder of the layered structure along the stacking direction, resulting in a portion of Mg 2+ Exposure and release of ions. Once the electric field is applied, a high concentration of TBA on the crystal surface + Ions will gradually replace Mg 2+ ion.
[0134] Fig.18 Mg4C in the intercalation process of the present invention 60 Atomic scale diagram of a crystal. Fig.18 As shown in Figure 2, when the interlayer spacing is enlarged to a large extent, the Mg and C 60 The atomic ratio dropped from 4.03 to 1.83.
[0135] In order to characterize the 2D C 60 The charge states on the networks were analyzed by X-ray photoelectron spectroscopy (XPS) and zeta potential. Fig.19 Mg4C 60 Zeta potential and XPS diagram of the crystal, Fig.19 a in the figure is the Zeta potential graph, and b is the XPS graph. Fig.19 As shown in a, the two-dimensional C 60 The zeta potential of the network is -35.2 mV, confirming the presence of surface charges, such as Fig.19 As shown in b, XPS analysis shows that the two-dimensional C 60 Residual Mg on the network surface 2+ , and the characteristic N1s peak of the ammonium group at 400.8 eV was observed, indicating that Mg 2+ The ion part was TBA + ions replaced.
[0136] However, the 2D C 60 The large amount of counterions remaining on the network is not conducive to optoelectronic devices because these ions destroy the ideal band alignment, reduce carrier mobility and increase the charge recombination rate. Hydrogen peroxide (H2O2) was used to quench these negative charges, neutralizing the average Zeta potential to -5.1 mV. High-resolution XPS spectroscopy confirmed that the quenched 2D C 60There are no sp hybridized CN (286.8 eV), N 1s (400.8 eV) and Mg 1s (1304.7 eV) peaks on the network surface, indicating that TBA + and Mg 2+ The ions are completely removed.
[0137] In order to study these two-dimensional C 60 The photoelectric characteristics of the network, the present invention uses a simple filtering device to make a planar thin film photoelectric detector, including the following steps:
[0138] S1. Provide a doped silicon substrate.
[0139] S2. Coat a SiO2 layer on the doped silicon substrate. The thickness of the SiO2 layer is 300 nm. Use photolithography technology to prepare a patterned drain and source on the SiO2 layer.
[0140] S3, using vacuum filtration method, the two-dimensional C 60 The network was prepared on a porous polytetrafluoroethylene filter to obtain a two-dimensional C 60 Network film, 2D C 60 The network film has a thickness of 200 nm and is then transferred to the SiO2 layer to prepare a photodetector having a channel width of 200 μm and a length of 10 μm.
[0141] Fig. 20 The two-dimensional C 60 Photocurrent response diagram of the network film photodetector. Fig. 20 As shown, with the molecule C 60 Photodetectors are different, based on two-dimensional C 60 The device with the network exhibits a significant photocurrent response under near-infrared (NIR) light. This is due to the formation of intermolecular covalent bonds that shorten the C 60 distance between cells, thereby enhancing electronic coupling.
[0142] In addition, the 2D C 60 The network thin film photodetector obtains a wider spectrum of photoelectric response, ranging from the visible light region (405nm) to the NIR region (1200nm). Fig.21 The two-dimensional C 60 Photoelectric response diagram of network thin film photodetector in different bands. Fig.21 As shown in Figure 2, under visible light irradiation, a photogenerated current of about 15 nA was observed, which was slightly higher at 625 nm to 20 nA. It is worth noting that the photogenerated current at 850 nm reached 30 nA, which is 50% higher than that under visible light. Compared with single-component materials such as ZnTCPP (400 nm to 600 nm), TpEtBr COF (446 nm) and BT-Py BuOH(420nm) compared to 2D C 60 The network exhibits superior broad-spectrum photoelectric response, especially with enhanced photoresponse in the NIR region. Importantly, this photoresponse behavior is relatively stable and reproducible, independent of the wavelength of light.
[0143] Fig. 22 The two-dimensional C 60 The performance diagram of the photocurrent of the network thin film photodetector under different voltage and light intensity changes. Fig. 22 As shown in the upper part of , the photogenerated current increases significantly with the increase of applied voltage, which can be attributed to the increase in the transmission speed of photogenerated carriers with the increase of electric field intensity. Fig. 22 As shown in the lower part of the graph, at 850nm, the increase in light intensity obviously leads to an enhancement in the photogenerated current.
[0144] Fig.23 The two-dimensional C 60 The photoelectric response intensity diagram of the network thin film photodetector under different voltages. Fig.23 As shown in , it shows a trend consistent with the photogenerated current. Measurements under illumination of different wavelengths confirmed this relationship, which follows a power law dependence on light intensity (I p ∝P α ). The fitting exponent of α≈0.69 can be derived from the complex process of electron-hole generation, capture, and recombination in the semiconductor, or from the photoelectric mechanism. This behavior can also be affected by factors such as interface defects between the semiconductor and the substrate. Using R∝P -(1-α) The corresponding photoelectric response intensity can also be well fitted.
[0145] It can be seen from this that the two-dimensional C 60 The broad spectral response of the network originates from the highly delocalized π-conjugated system within its symmetrical cage structure, which allows photon absorption across the ultraviolet, visible, and near-infrared regions. The high molecular symmetry enhances its optical response by enabling multiple absorption bands across different spectral regions. In addition, its modest energy gap promotes the formation of excitons and electronic transitions over a broad spectrum, supported by various electronic and orbital coupling effects. The results show that the exfoliated 2D C 60 Networks are feasible for fabricating large-scale, cost-effective, broadband photonic devices.
[0146] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0147] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A method for electrochemical synthesis of a two-dimensional fullerene covalent network, characterized in that: The following steps are involved: Using fullerene superlattice material as cathode, inert material as anode, and a mixed solution of quaternary ammonium salt containing hydrogen protons and polar aprotic solvent as electrolyte solution, electrochemical stripping is carried out under constant voltage. Through the auxiliary effect of in-situ reduction of hydrogen ions driven by electric field and uniform intercalation of quaternary ammonium salt cations, a two-dimensional fullerene covalent network is obtained.
2. The electrochemical synthesis method of the two-dimensional fullerene covalent network according to claim 1, characterized in that: The concentration of the quaternary ammonium salt containing hydrogen protons in the electrolyte solution is 3 mg / mL to 20 mg / mL.
3. The electrochemical synthesis method of the two-dimensional fullerene covalent network according to claim 1, characterized in that: The hydrogen proton-containing quaternary ammonium salt is at least one of tetra-n-butylammonium hydrogen sulfate, tetra-n-butylammonium hydrogen phosphate, tetra-n-butylammonium hydrogen carbonate, tetra-n-butylammonium hydroxide, and tetra-n-butylammonium hydrofluoride; and the polar aprotic solvent is at least one of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, N-methylpyrrolidone, 1,3-dimethyl-2-imidazolidinone, propylene carbonate, and acetonitrile.
4. The electrochemical synthesis method of the two-dimensional fullerene covalent network according to claim 1, characterized in that: The potential of the constant voltage is -4V to -12V, the stripping temperature is -50°C to 200°C, and the stripping time is 2h to 8h.
5. The electrochemical synthesis method of the two-dimensional fullerene covalent network according to claim 1, characterized in that: The fullerene superlattice material is an alkaline earth metal-doped fullerene covalently assembled superlattice with a layered structure.
6. The electrochemical synthesis method of the two-dimensional fullerene covalent network according to claim 5, characterized in that: The alkaline earth metal is Mg, Li, Na, K or Rb.
7. The electrochemical synthesis method of a two-dimensional fullerene covalent network according to claim 1, characterized in that: The fullerene superlattice material is embedded in a porous metal foam support as the cathode.
8. The electrochemical synthesis method of a two-dimensional fullerene covalent network according to claim 1, characterized in that: The electrochemical stripping adopts a two-electrode or three-electrode system. After the electrochemical stripping, the stripped product is shaken and centrifuged at 800rpm to 1200rpm for 3min to 15min to obtain an initial product, and then a H2O2 solution with a mass concentration of 2% to 5% is added for charge quenching, and the product is centrifuged at 3000rpm to 12000rpm for 3min to 15min to obtain a two-dimensional fullerene covalent network.
9. A two-dimensional fullerene covalent network prepared by the electrochemical synthesis method according to any one of claims 1 to 8, characterized in that: The lateral size of the two-dimensional fullerene covalent network is 0.1 μm to 100 μm, and the average thickness is 0.8 nm to 10 nm.
10. A photoelectric detector, characterized in that: The two-dimensional fullerene covalent network described in claim 9 is used as a photoelectric response element for preparation.
Citation Information
Patent Citations
Method for preparing graphene energy storing material through electrochemical cathodic disbonding
CN102923697A
Method for stripping ferric thiophosphate crystal synchronously doped monatomic by electrochemical assistance
CN113880060A
Method for preparing controllable graphene by regulating and controlling ion intercalation through electrode and magnetic field
CN114195140A
Electrode and sensor having carbon nanostructures
US20100252450A1
Two-dimensional carbon materials prepared by electrochemical exfoliation
WO2015158711A1
Cited By
Two-dimensional fullerene and alkali metal intercalation stripping method and application thereof
CN121020566A
A two-dimensional fullerene and its alkali metal intercalation exfoliation method and application
CN121020566B